Evaluation of adjacent and opposite current injection patterns for a wearable chest electrical impedance tomography system - Yang, Lin; Gao, Zhijun; Wang, Chunchen; Wang, Hang; Dai, Jing; Liu, Yang; Qin, Yilong; Dai, Meng; Cao, Xinsheng; Zhao, Zhanqi (Physiological measurement, 2024)
Objective. Wearable electrical impedance tomography (EIT) can be used to monitor regional lung ventilation and perfusion at the bedside. Due to its special system architecture, the amplitude of the injected current is usually limited compared to stationary EIT system. This study aims to evaluate the performance of current injection patterns with various low-amplitude currents in healthy volunteers. Approach. A total of 96 test sets of EIT measurement was recorded in 12 healthy subjects by employing adjacent and opposite current injection patterns with four amplitudes of small current (i.e. 1 mA, 500 uA, 250 uA and 125 uA). The performance of the two injection patterns with various currents was evaluated in terms of signal-to-noise ratio (SNR) of thorax impedance, EIT image metrics and EIT-based clinical parameters. Main results. Compared with adjacent injection, opposite injection had higher SNR ( p < 0.01), less inverse artifacts ( p < 0.01), and less boundary artifacts ( p < 0.01) with the same current amplitude. In addition, opposite injection exhibited more stable EIT-based clinical parameters ( p < 0.01) across the current range. For adjacent injection, significant differences were found for three EIT image metrics ( p < 0.05) and four EIT-based clinical parameters ( p < 0.01) between the group of 125 uA and the other grou p s. Significance. For better performance of wearable pulmonary EIT, currents greater than 250 uA should be used in opposite injection, 500 uA in adjacent one, to ensure a high level of SNR, a high quality of reconstructed image as well as a high reliability of clinical parameters.